Microtubule inner proteins of Plasmodium are essential for transmission of malaria parasites - Hentzschel, Franziska; Binder, Annika M.; Dorner, Lilian; Herzel, Lea; Nuglisch, Fenja; Sema, Meslo; Röver, Katharina; He, Buyuan; Aguirre-Botero, Manuela C.; Cyrklaff, Marek; Funaya, Charlotta; Frischknecht, Friedrich (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Microtubule inner proteins (MIPs) are microtubule-associated proteins that bind to tubulin from the luminal side. MIPs can be found in axonemes to stabilize flagellar beat or within cytoplasmic microtubules. Plasmodium spp. are the causative agents of malaria that feature different parasite forms across a complex life cycle with both unique and divergent microtubule-based arrays. Here, we investigate four MIPs in a rodent malaria parasite for their role in transmission to and from the mosquito. We show by single and double gene deletions that SPM1 and TrxL1, MIPs associated with subpellicular microtubules, are dispensable for transmission from the vertebrate host to the mosquito and back. In contrast, FAP20 and FAP52, MIPs associated with the axonemes of gametes, are essential for transmission to mosquitoes but only if both genes are deleted. In the absence of both FAP20 and FAP52, the B-tubule of the axoneme partly detaches from the A-tubule, resulting in the deficiency of axonemal beating and hence gamete formation and egress. Our data suggest that a high level of redundancy ensures microtubule stability in the transmissive stages of Plasmodium, which is important for parasite transmission.